Diversified mcr-1-Harbouring Plasmid Reservoirs Confer Resistance to Colistin in Human Gut Microbiota - Huiyan Ye (American Society for Microbiology, 2016)
ABSTRACT Colistin is an ultimate line of refuge against multidrug-resistant Gram-negative pathogens. Very recently, the emergence of plasmid-mediated mcr-1 colistin resistance has become a great challenge to global public health, raising the possibility that dissemination of the mcr-1 gene is underestimated and diversified. Here, we report three cases of plasmid-carried MCR-1 colistin resistance in isolates from gut microbiota of diarrhea patients. Structural and functional analyses determined that the colistin resistance is conferred purely by the single mcr-1 gene. Genetic and sequence mapping revealed that mcr-1-harbouring plasmid reservoirs are present in diversity. Together, the data represent the first evidence of diversity in mcr-1-harbouring plasmid reservoirs of human gut microbiota. IMPORTANCE The plasmid-mediated mobile colistin resistance gene (mcr-1) challenged greatly the conventional idea mentioned above that colistin is an ultimate line of refuge against lethal infections by multidrug-resistant Gram-negative pathogens. It is a possibility that diversified dissemination of the mcr-1 gene might be greatly underestimated. We report three cases of plasmid-carried MCR-1 colistin resistance in isolates from gut microbiota of diarrhea patients and functionally define the colistin resistance conferred purely by the single mcr-1 gene. Genetic and sequence mapping revealed unexpected diversity among the mcr-1-harbouring plasmid reservoirs of human gut microbiota.